Hematology profile of Pengging duck (Anas javanica) in starter period in response to Lactobacillus Salivarius I-11 probiotics as a feed additive and an alternative to replace antibiotics - Sumarsih, Sri; Sulistiyanto, Bambang; Utama, Cahya Setya (Journal of Advanced Veterinary Research, 2025)
The study was conducted with the purpose of studying the hematology profile of Pengging Duck (Anas javanica) in starter period given with probiotic Lactobacillus salivarius I-11 as feed additives as an alternative to replace antibiotics. The completely randomized design with 4, 5 replications and 10 units. There were 200 DOD male Pengging Ducks that are classified into 4 different treatments, that were: Treatment P0= Control, P1= Antibiotics, P2= 1 ml Probiotics Lactobacillus salivarius I-11; P3= 2 ml Probiotics Lactobacillus salivarius I-11. The parameters were duck blood profiles (in terms of the number of erythrocytes, leucocytes, hemoglobin and hematocrit) and lymphocyte cell types (lymphocytes, heterophil and heterophil-lymphocytes ratio). Statistical analysis showed that control ducks had significantly lower amounts of erythrocytes, leucocytes, hemoglobin and hematocrit (P <0.05) than those that were given antibiotics and probiotics. The result of statistical analysis showed that duck treated with Lactobacillus salivarius I-11 had percentage of lymphocyte cell and ratio of real lymphocyte heterophil (p < 0.05) lower than the control treatment group, but it is not significantly different in comparison to the antibiotics treatments. Providing I ml of Lactobacillus salivarius I-11 probiotics as feed additives can replace the use of antibiotics in ducks during the starter period which was observed from their hematological profile.